Why Does Agricultural Growth Dominate Poverty Reduction in Low- and Middle-income Countries? (The Pakistan Development Review, 2006)
“Alternative models have to compete on the basis of their ability to give a satisfying account of some facts. Facts ask for explanations, and explanations ask for new facts”. Robert M. Solow, Daedalus (Fall 2005) This paper provides an explanation of the relation between agricultural growth and poverty reduction for open economies with full employment. The analysis also shows that the poverty-reducing impact of agricultural growth in an open economy is far greater if there is unemployed labour or if the supply of labour is highly elastic—conditions often thought to prevail even in open economies. The model draws attention to the critical role of the rural non-tradable sector in poverty reduction. While ample data are available to show that sector to have a large share of employment, even relative to agriculture itself, data for other variables for the sector such as the share of GDP, labour intensity, price, and income elasticities of demand are not available. Thus, an important contribution of the paper is to establish the need for such data if the processes of poverty reduction are to be understood. JEL classification: Q01, I30 Keywords: Agricultural Growth, Poverty, Developing Countries, Open Economy